Influence of nanoscale deformation twins near a slant edge crack tip on crack blunting in nanocrystalline metals. (15th October 2017) - He, Tengwu; Feng, Miaolin
Highlights: Interaction between a slant edge crack and nanoscale deformation twin. Expressions of the critical SIFs for the first lattice dislocation emission from the slant edge crack tip are obtained. Analyze the effects of the crack length, the inclined angle of the crack, the relative thickness of nanoscale twin band and different nanocrystalline materials on the SIFs. Abstract: A theoretical model is developed that discusses the effect of nanoscale deformation twins on dislocation emission from the tip of slant edge crack in nanocrystalline materials. By combining complex variable method of Muskhelishvili and conformal mapping technique, the explicit solutions of complex potentials are obtained analytically. The critical stress intensity factors (SIFs) for the emission of first lattice edge dislocation from a slant edge crack tip are calculated. The effects of vital parameters such as the crack length, the inclined angle of the crack, the relative thickness of the nanotwin on critical SIFs for dislocation emission are evaluated in detail. The results show that the emission of lattice dislocation from the slant edge crack tip is significantly influenced by nanoscale deformation twins. The smaller the inclined angle is, the more difficult it is for dislocation emission from the slant edge crack tip. Particularly, the dislocation near the tip of slant edge crack is prone to emit when the inclined angle of the crack is about 45°. As a special case, when the inclined angle of slant edge crack is 0°, the present results will reduce to those of the problem of nanoscale deformation twins interacting with mode I straight crack.